2013
DOI: 10.1073/pnas.1302918110
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ubiquitin-dependent cargo sorting by multiple endocytic adaptors at the plasma membrane

Abstract: Endocytic protein trafficking is directed by sorting signals on cargo molecules that are recognized by cytosolic adaptor proteins. However, the steps necessary to segregate the variety of cargoes during endocytosis remain poorly defined. Using Caenorhabditis elegans, we demonstrate that multiple plasma membrane endocytic adaptors function redundantly to regulate clathrin-mediated endocytosis and to recruit components of the endosomal sorting complex required for transport (ESCRT) machinery to the cell surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 44 publications
6
94
1
Order By: Relevance
“…Epsin favors binding to K63-polyubiquitin, which correlates well with the requirement of multiple Ubs as an internalization signal (Hawryluk et al 2006;Sato et al 2009). Other UBDs are present at sites of CME including ones in CIN85 and Hrs, and others are likely to be uncovered (Soubeyran et al 2002;Stamenova et al 2007;Mayers et al 2013). Because relatively few proteins have been assessed for Ub-dependent internalization, it is possible that these additional UBD-containing proteins operate as adaptors for different subsets of ubiquitinated proteins.…”
Section: How Ubiquitin Mediates Internalization From the Plasma Membranementioning
confidence: 99%
“…Epsin favors binding to K63-polyubiquitin, which correlates well with the requirement of multiple Ubs as an internalization signal (Hawryluk et al 2006;Sato et al 2009). Other UBDs are present at sites of CME including ones in CIN85 and Hrs, and others are likely to be uncovered (Soubeyran et al 2002;Stamenova et al 2007;Mayers et al 2013). Because relatively few proteins have been assessed for Ub-dependent internalization, it is possible that these additional UBD-containing proteins operate as adaptors for different subsets of ubiquitinated proteins.…”
Section: How Ubiquitin Mediates Internalization From the Plasma Membranementioning
confidence: 99%
“…Interestingly, Mayers et al (2013) identified a FEI complex that seems to recruit ESCRT-0 to a subset of clathrin coated pits on the plasma membrane in Caenorhabditis elegans. Loss of the complex does not affect the overall rate of clathrin-mediated endocytosis but specifically inhibits degradation of lysosomal cargo.…”
Section: Tols: Coupling Endocytosis and Lysosomal Degradationmentioning
confidence: 99%
“…Because CAV-1-GFP contains 34 lysine residues in its cytosolic region, it could be ubiquitylated at multiple sites. In fact, a recent study using mass spectrometry suggested that at least two lysine residues in GFP-CAV-1 are ubiquitylated in embryos (Mayers et al, 2013). To confirm that the smeared bands corresponded to the ubiquitylated form, CAV-1-GFP was immunoprecipitated from embryo lysates and probed with an anti-ubiquitin antibody (Fig.…”
Section: Cav-1-gfp Is Ubiquitylated After Fertilizationmentioning
confidence: 99%